Attitudes, challenges and needs about diet and physical activity in endometrial cancer survivors: a qualitative study. (21st June 2016) - Koutoukidis, D.A.; Beeken, R.J.; Lopes, S.; Knobf, M.T.; Lanceley, A.
Abstract : With rates of endometrial cancer survival increasing, there is growing interest about lifestyle behaviours that could improve quality of life and reduce the risk for chronic diseases. This study aimed to explore the attitudes, challenges and needs of endometrial cancer survivors regarding diet and physical activity. Sixteen UK‐based endometrial cancer survivors participated in two focus groups (n = 5, n = 3) or individual telephone interviews (n = 8), using a semi‐structured interview guide. Data were collectively analysed by two researchers until consensus was reached on a coding structure. Data analysis proceeded until themes were identified. Participants were within 5 years post‐cancer treatment with median age and BMI of 57 years and 25.8 kg m −2 respectively. Three themes were identified: (1) defining a healthy lifestyle, (2) factors influencing diet and physical activity and (3) needing to search for information. Results suggest interventions should incorporate recommendations on managing late‐treatment effects, and behaviour change techniques for cognitive, practical and social barriers to healthy lifestyle changes. Healthcare professionals are in a vital position to provide or introduce endometrial cancer survivors to in‐person behaviour change interventions at the early post‐treatment period.